The distribution of refractive errors among children attending Lumbini Eye Institute, Nepal - Rai, S KC; Thapa, HB; Sharma, MK; Dhakhwa, K; Karki, R (Nepalese Journal of Ophthalmology, 2012)
Introduction: Uncorrected refractive error is an important cause of childhood blindness and visual impairment. Objective: To describe the patterns of refractive errors among children attending the outpatient clinic at the Department of Pediatric Ophthalmology, Lumbini Eye Institute, Bhairahawa, Nepal. Subjects and methods: Records of 133 children with refractive errors aged 5 - 15 years from both the urban and rural areas of Nepal and the adjacent territory of India attending the hospital between September and November 2010 were examined for patterns of refractive errors. The SPSS statistical software was used to perform data analysis. Results: The commonest type of refractive error among the children was astigmatism (47 %) followed by myopia (34 %) and hyperopia (15 %). The refractive error was more prevalent among children of both the genders of age group 11-15 years as compared to their younger counterparts (RR = 1.22, 95 % CI = 0.66 – 2.25). The refractive error was more common (70 %) in the rural than the urban children (26 %). The rural females had a higher (38 %) prevalence of myopia than urban females (18 %). Among the children with refractive errors, only 57 % were using spectacles at the initial presentation. Conclusions: Astigmatism is the commonest type of refractive error among the children of age 5 - 15 years followed by hypermetropia and myopia. Refractive error remains uncorrected in a significant number of children. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5858 NEPJOPH 2012; 4(1): 90-95